Draft Annual Plan 1978-79 Government of Bihar - Planning Commission (Planning Commission, 1978)
Bihar's Population of 56.35 millions, according to 1971 Cebsus, accounts for 10.3 per cent of the population of India. Comprised in 1.74 lakh square kms it accounts for 5.3 per cent of the area of the country. Bihar is predominantly a pural State with 89.96 per cent of its population living in villages against the all-India percentage of 80.13 per cent of the tatal number of workers in the State is agriculture. 6.81 millions, constituting 38.92 per cent of the tatal working force are agricultural labourers. The proportion of agricultural labourers to the working force inereased from 22.97 per cent in 1961 to 38.92 per cent in 1971.
Planning Department Government of Bihar